Aloe-emodin triggers ROS and Ca 2+ production and decreases the levels of mitochondrial membrane potential of human brain capillary endothelial cells - Ivanka Dimova; Svetla Danova; Ekaterina Nikolova; Miglena Koprinarova (International Journal of Phytomedicine, 2017)
The aim of this work was to investigate the mechanisms of cytotoxicity of phyto-hydroxyanthraquinone aloe-emodin (AE) on human brain microvascular endothelial cell line hCMEC/D3 and to assess the cellular response in the early stage of treatment in order to extend the knowledge of AE’s anti-angiogenic properties. The immortalized human brain capillary endothelial cells hCMEC/D3 were treated with a series of AE concentrations (5 - 200 μM) for a period of 24 hours. The cell viability was determined by MTS assay. The cellular adenosine triphosphate (ATP) levels were evaluated by CellTiter-Glo® luminescent assay. The intracellular reactive oxygen species (ROS) were determined by 2’,7’-dichlorofluorescein (CM- H2DCFDA) fluorescence assay. The mitochondrial membrane potential (MMP) was assessed using tetramethylrhodamine methyl ester (TMRM) staining, while Fluo-4 was used to measure 2 the intracellular free Ca 2+ concentrations inside living cells analysed by High Content Analysis using the Arrayscan VTI 740. Twenty-four- hour treatment of hCMEC/D3 cells with AE, in concentrations between 50 and 200 µM, decreased the cell viability as well as the intracellular ATP levels in a dose- dependent manner. Increased ROS production and disruption of the mitochondrial membrane potential have also been detected. Notably, AE at a concentration greater than 5 µM dramatically increased intracellular calcium levels. Our results collectively indicate that AE inhibits proliferation of human brain microvascular cells via a mechanism involving ROS generation, disruption of Ca 2+ homeostasis and mitochondrial damage.